The Experimental Investigation Of a New Design of Stirred Media Mill - Baigereyev, Samat; Guryanov, Georgiy; Vasilyeva, Ol'ga (Eurasian Journal of Applied Engineering and Technology (EJAET), 2023)
With the rapid development of nanotechnology, the need to improve the efficiency of material grinding processes has increased. One of the criteria for the effectiveness of the process is the product fineness. There are various types of mills for grinding materials, one of which is stirred media mills. The article presents the results of experimental studies of a new design of stirred media mill on the example of sand particles size reduction. The principle of operation of the new mill is based on the organization of complex radial and axial impact on the particles of the material by grinding balls. To ensure this principle, a typical stirred media mill design includes an ellipsoidal rotor and a vibratory drive with springs. The results of the study demonstrated that the maximal product fineness of the mill with an initial sand particle size of 100 µm accounted for 2.32 µm, which is 2.6 times higher than the product fineness obtained in typical stirred media mill designs.